2017
DOI: 10.1016/j.jconhyd.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization and prolonged reactivity of aqueous-phase ozone with cyclodextrin

Abstract: Recalcitrant organic groundwater contaminants, such as 1,4-dioxane, may require strong oxidants for complete mineralization. However, their efficacy for in-situ chemical oxidation (ISCO) is limited by oxidant decay and reactivity. Hydroxypropyl-β-cyclodextrin (HPβCD) was examined for its ability to stabilize aqueous-phase ozone (O) and prolong oxidation potential through inclusion complex formation. Partial transformation of HPβCD by O was observed. However, HPβCD proved to be sufficiently recalcitrant, becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…S7), which has been reported previously with other guest molecules and has been explained in terms of a change in the environment of the molecule as it is included within the CD cavity (Hendy and Breslin, 2011;Lin et al, 2020). Usually, O3 would have been completely degraded after 1-3 hour in DI water (Dettmer et al, 2017), however in this study, absorption peaks were still observed even after 12 h in the presence of HPβCD (Fig 5a and Fig. S7).…”
Section: Characterisation Of Inclusion Complexessupporting
confidence: 80%
See 3 more Smart Citations
“…S7), which has been reported previously with other guest molecules and has been explained in terms of a change in the environment of the molecule as it is included within the CD cavity (Hendy and Breslin, 2011;Lin et al, 2020). Usually, O3 would have been completely degraded after 1-3 hour in DI water (Dettmer et al, 2017), however in this study, absorption peaks were still observed even after 12 h in the presence of HPβCD (Fig 5a and Fig. S7).…”
Section: Characterisation Of Inclusion Complexessupporting
confidence: 80%
“…2a and Table 1). As the hydroxypropyl group of HPβCD could be oxidised, the ring in glycosides remains stable in the presence of oxidants, including O3 (Manhas et al, 2007;Dettmer et al, 2017). Addition of small amounts of HPβCD, e.g.…”
Section: Improved Stabilisation Of O3 By Hpβcd Inclusion Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…This unique arrangement gives CDs the ability to form inclusion complexes with low-polarity molecules of appropriate size and shape . CDs have been utilized in an increasingly wide range of applications such as drug carriers, oil recovery, cosmetics, , agriculture, analytical chemistry, and aquifer remediation. …”
Section: Introductionmentioning
confidence: 99%